Education on Herbal Antibacterial Properties of Moringa and Moringa Tea Training - , Zehklafh Lattenni; Allloptino Latnhi (Akademi Sertifikasi Profesi Internasional, 2024)
Bacterial infections and drug resistance constitute significant health issues in Indonesia. The general lack of awareness regarding the proper use of antibiotics is one of the main causes. Therefore, the Community Service team from the Health Analyst Study Program conducted an activity titled